Characterization and assessment of potential microRNAs involved in phosphate‐induced aortic calcification. Issue 5 (16th November 2017) - Fakhry, Maya; Skafi, Najwa; Fayyad‐Kazan, Mohammad; Kobeissy, Firas; Hamade, Eva; Mebarek, Saida; Habib, Aida; Borghol, Nada; Zeidan, Asad; Magne, David; Fayyad‐Kazan, Hussein; Badran, Bassam
Abstract : Medial artery calcification, a hallmark of type 2 diabetes mellitus and chronic kidney disease (CKD), is known as an independent risk factor for cardiovascular mortality and morbidity. Hyperphosphatemia associated with CKD is a strong stimulator of vascular calcification but the molecular mechanisms regulating this process remain not fully understood. We showed that calcification was induced after exposing Sprague‐Dawley rat aortic explants to high inorganic phosphate level (Pi, 6 mM) as examined by Alizarin red and Von Kossa staining. This calcification was associated with high Tissue‐Nonspecific Alkaline Phosphatase (TNAP) activity, vascular smooth muscle cells de‐differentiation, manifested by downregulation of smooth muscle 22 alpha (SM22α) protein expression which was assessed by immunoblot analysis, immunofluorescence, and trans‐differentiation into osteo‐chondrocyte‐like cells revealed by upregulation of Runt related transcription factor 2 (Runx2), TNAP, osteocalcin, and osteopontin mRNA levels which were determined by quantitative real‐time PCR. To unravel the possible mechanism(s) involved in this process, microRNA (miR) expression profile, which was assessed using TLDA technique and thereafter confirmed by individual qRT‐PCR, revealed differential expression 10 miRs, five at day 3 and 5 at day 6 post Pi treatment versus control untreated aortas. At day 3, miR‐200c, ‐155, 322 were upregulated and miR‐708 and 331 were downregulated. After 6 days of treatment, miR‐328, ‐546, ‐301a were upregulated while miR‐409 and miR‐542 were downregulated. Our results indicate that high Pi levels trigger aortic calcification and modulation of certain miRs. These observations suggest that mechanisms regulating aortic calcification might involve miRs, which warrant further investigations in future studies. Abstract : Our results indicate that high Pi levels trigger aortic calcification and modulation of certain miRs.